Histone Deacetylase 7 Inhibition in a Murine Model of Gram-Negative Pneumonia-Induced Acute Lung Injury. Issue 3 (March 2020) - Kasotakis, George; Kintsurashvili, Ekaterina; Galvan, Manuel D.; Graham, Christopher; Purves, J. Todd; Agarwal, Suresh; Corcoran, David L.; Sullenger, Bruce A.; Palmer, Scott M.; Remick, Daniel G.
ABSTRACT: Background: Pulmonary infections remain the most common cause of Acute Respiratory Distress Syndrome (ARDS), a pulmonary inflammatory disease with high mortality, for which no targeted therapy currently exists. We have previously demonstrated an ameliorated syndrome with early, broad spectrum Histone Deacetylase (HDAC) inhibition in a murine model of gram-negative pneumonia-induced Acute Lung Injury (ALI), the underlying pulmonary pathologic phenotype leading to ARDS. With the current project we aim to determine if selective inhibition of a specific HDAC leads to a similar pro-survival phenotype, potentially pointing to a future therapeutic target. Methods: C57Bl/6 mice underwent endotracheal instillation of 30×10 6 Escherichia coli (strain 19138) versus saline (n = 24). Half the infected mice were administered Trichostatin A (TSA) 30 min later. All animals were sacrificed 6 h later for tissue sampling and HDAC quantification, while another set of animals (n = 24) was followed to determine survival. Experiments were repeated with selective siRNA inhibition of the HDAC demonstrating the greatest inhibition versus scrambled siRNA (n = 24). Results: TSA significantly ameliorated the inflammatory phenotype and improved survival in infected-ALI mice, and HDAC7 was the HDAC with the greatest transcription and protein translation suppression. Similar results were obtained with selective HDAC7 siRNA inhibition compared with scrambled siRNA. Conclusion: HDAC7 appears to play a key role in the inflammatory response that leads to ALI after gram-negative pneumonia in mice. Abstract : Supplemental Digital Content is available in the text